High-frequency filtering for low-temperature thermal transport studies in nanostructures - Torgovkin, Andrii (2012)
Filtering of external unwanted RF-noise and thermal noise generated at the high-temperature parts of the measuring circuit is essential for successful measurements of thermal transport of nanostructures at low temperatures. This is because of thermal decoupling of the systems, i.e. the extreme weakness of thermal conduction at sub-Kelvin temperatures, leading easily to overheating even with excess power in sub pW range. We have started to improve the noise filtering in our cryogenic dilution refrigerators, which can reach a base temperature of ~ 50 mK. The miniature low-pass filters were made from special RF sealing compound Eccosorb CR124, stainless steel powder of grain size 50 micrometers and a typical low-temperature epoxy (Stycast). Measured cut-off frequency is at 1 MHz, low enough to cut most of the radiated RF power.